Inflammatory Markers in Middle-Aged Obese Subjects: Does Obstructive Sleep Apnea Syndrome Play a Role? - Paschalis Steiropoulos; Nikolaos Papanas; Evangelia Nena; Maria Antoniadou; Evangelia Serasli; Sophia Papoti; Olga Hatzizisi; Georgios Kyriazis; Argyris Tzouvelekis; Efstratios Maltezos; Venetia Tsara; Demosthenes Bouros (Hindawi Limited, 2010)
Background. Obstructive Sleep Apnea Syndrome (OSAS) is associated with inflammation, but obesity may be a confounding factor. Thus, the aim of this study was to explore differences in serum levels of inflammation markers between obese individuals with or without OSAS. Methods. Healthy individuals (n=61) from an outpatient obesity clinic were examined by polysomnography and blood analysis, for measurement of TNF-α, IL-6, CRP, and fibrinogen levels. According to Apnea-Hypopnea Index (AHI), participants were divided into two BMI-matched groups: controls (AHI < 15/h, n=23) and OSAS patients (AHI ≥ 15/h, n=38). Results. OSAS patients had significantly higher TNF-α levels (P<.001) while no other difference in the examined inflammation markers was recorded between groups. Overall, TNF-α levels were correlated with neck circumference (P<.001), AHI (P=.002), and Oxygen Desaturation Index (P=.002). Conclusions. Obese OSAS patients have elevated TNF-α levels compared to BMI-matched controls, suggesting a role of OSAS in promoting inflammation, possibly mediated by TNF-a.